Neurological Implications and Effects on Language Development (Docentes 2.0 Journal, 2021)
Language, from its conception as a communication system, is shown to be involved in all areas of the human being. In particular, in the educational processes, where it forms the basis of any learning. Despite this, little research has been done on language disorders at the neurological level. With this objective in mind, this article carried out a theoretical study regarding the neural characters involved in the development of human speech, as well as the most common problems that arise in this area. In this way, it was sought to provide educators with theoretical support that allows them to guide their procedures when treating conditions of this type in students of formal education, especially through didactic strategies based on the plasticity of the brain and its ability to be molded.
Keywords: Disorders; language; neuronal; neuroplasticity; stimulation; education